PLAYFUL TECHNICAL ACTIVITIES DURING PREPARING THE KINDERGARTEN TEACHERS - Miroslav, JANU; KVAPIL, Ludek (Trends in education, 2009)
This article deals with the problems of aims, content and implementation if the subject "Playful Technical Activities" during preparing the kindergarten teachers.
Keywords: Playful technical activities; toy; natural material; metallic materials.